New Triazinoindole Bearing Benzimidazole/Benzoxazole Hybrids Analogs as Potent Inhibitors of Urease: Synthesis, In Vitro Analysis and Molecular Docking Studies - Sundas Mumtaz; Shahid Iqbal; Mazloom Shah; Rafaqat Hussain; Fazal Rahim; Wajid Rehman; Shoaib Khan; Obaid-ur-Rahman Abid; Liaqat Rasheed; Ayed A. Dera; Hanan A. Al-ghulikah; Sana Kehili; et al. (Molecules, 2022)
Twenty-four analogs based on triazinoindole bearing benzimidazole/benzoxazole moieties (1–25) were synthesized. Utilizing a variety of spectroscopic methods, including 1H-, 13C-NMR, and HREI-MS, the newly afforded compounds (1–25) were analyzed. The synthesized analogs were tested against urease enzyme (in vitro) as compared to the standard thiourea drug. All triazinoindole-based benzimidazole/benzoxazole analogs (1–25) exhibited moderate to excellent inhibition profiles, having IC50 values of 0.20 ± 0.01 to 36.20 ± 0.70 μM when evaluated under the positive control of thiourea as a standard drug. To better understand the structure–activity relationship, the synthesized compounds were split into two groups, “A” and “B.” Among category “A” analogs, analogs 8 (bearing tri-hydroxy substitutions at the 2,4,6-position of aryl ring C) and 5 (bearing di-hydroxy substitutions at the 3,4-position of aryl ring C) emerged as the most potent inhibitors of urease enzyme and displayed many times more potency than a standard thiourea drug. Besides that, analog 22 (which holds di-hydroxy substitutions at the 2,3-position of the aryl ring) and analog 23 (bearing ortho-fluoro substitution) showed ten-fold-enhanced inhibitory potential compared to standard thiourea among category “B” analogs. Molecular docking studies on the active analogs of each category were performed; the results obtained revealed that the presence of hydroxy and fluoro-substitutions on different positions of aryl ring C play a pivotal role in binding interactions with the active site of the targeted urease enzyme.